Dealing with facts in judicial process: A reflection of ijtihadic practice - Mohd Badrol, Awang; Mohd Lotpi, Mohd Yusob (2016)
The importance of understanding the factual reality (fahm al-waqi‘) has been widely recognized by Muslim jurists in their discussion relating to Islamic legal theory. It has been regarded as an important element for the practice of ijtihad and accepted as a valid justification for renewal of ijtihad. In light of the above, yet in a different context, the paper discusses the judicial concept of al-da‘wa and the significance of fahm al-waqi‘or understanding the fact of legal disputes (al-da‘awa) in Islamic judicial process. It examines the position of fahm al-waqi‘ in judicial process as well as the process that should be taken by the judges in dealing with the facts of the legal disputes. The study proves that, as in the process of formulating legal rulings (istinbat al-ahkam), understanding the facts of the cases assumes a very critical position in the judicial process, the ignorance of which will effect propriety of legal decisions and thus leading to injustice in decision making. Further, the paper argues that the process of understanding the fact of the case constitutes a form of ijtihad and that it must be undertaken by all judges regardless of their status whether they are mujtahid or muqallid.